STRATEGI MENGATASI KONFLIK DALAM MENGEMBANGKAN BUDAYA ASRAMA DI PONDOK PESANTREN - Sintia Noravika; Fadlilah Fadlilah; Fransisko Chaniago; Sizka Farwati (STKIP Pesisir Selatan, 2026)
This study aims to analyze conflict resolution strategies in developing dormitory culture at PKP Al-Hidayah Islamic Boarding School in Kota Baru District, Jambi Province. Conflicts in the dormitory arise due to differences in character, academic ability, habits, socio-cultural backgrounds, and psychological pressure experienced by the students. This study employs a descriptive qualitative approach, with data collected through observation, in-depth interviews, and related written documents. The findings indicate that conflicts in the dormitory environment are influenced by emotional factors, differences in academic ability, socio-cultural backgrounds and habits, as well as psychological pressure resulting from the boarding school’s disciplinary system. Conflict resolution strategies are implemented systematically through stages of conflict identification, persuasive and educational approaches, mediation, the application of guidance-oriented regulations, the reinforcement of Islamic values, and evaluation and follow-up. These strategies have proven effective in reducing conflict while simultaneously fostering a harmonious, disciplined dormitory culture grounded in Islamic values. This study affirms that conflict resolution in Islamic boarding schools is not solely oriented toward problem-solving, but also serves as a means of character education and continuous social development for students.